CURRENT STATE AND ANALYSIS OF TOURISM DEVELOPMENT IN RUSSIA UNTIL 2035 - Bushueva, Irina; Yudina, Elena (Revista Inclusiones, 2020)
Modern trends related to the development of domestic and inbound tourism make it necessary to improve the competitiveness of the tourism product that is offered in domestic and international tourism markets, as well as to create the most favorable conditions for the attraction of investment. For the purpose of attaining these goals, it is essential to measure a degree, in which a tourism product meets expectations of the target audience, to select areas contributing the most to the attainment of the targets, to determine priority areas, the development of which is inseparably linked with the tourism product, and to create conditions aimed to make businesses more interested in developing tourism on a comprehensive basis. The Tourism Development Strategy of the Russian Federation for the period until 2035 (referred to as the “Strategy”) aims to ensure comprehensive development of domestic and inbound tourism in the Russian Federation by creating conditions for the formation and promotion of a premium and competitive tourism product in the domestic and international tourism markets and to increase the social role of tourism and availability of tourism services, leisure and health improvement for Russian citizens.